The Pacific Meridional Mode as a trigger for ENSO in a high‐resolution coupled model. Issue 12 (18th June 2013) - Larson, Sarah; Kirtman, Ben
Abstract: [1] This study investigates El Niño precursors in a high‐resolution version of CCSM3.5. First, using an Empirical Orthogonal Function analysis of all non‐ENSO tropical Pacific variability, we find that the Pacific Meridional Mode (PMM) acts as an ENSO trigger 7–9 months prior to large El Niño events in the model, which is consistent with previous model and observational studies. However, because not every PMM event triggers an ENSO event, we also find that PMM appears to be an effective trigger when the western‐to‐central Pacific is preconditioned (i.e., anomalously high sea surface heights or heat content). Second, this study looks at the contribution of western Pacific variability, namely westerly wind bursts (WWBs), as well as all other non‐ENSO variability in the tropical Pacific. We find that the relative importance of low‐frequency climate variability associated with PMM dominates over other non‐ENSO variability between 15°N and 15°S, including high‐frequency atmospheric variability and WWBs, in acting as a precursor to El Niño events. Key Points: The dominant non‐ENSO variability in the tropical Pacific is PMM in a model PMM is an effective ENSO trigger when the equatorial Pacific is preconditioned Low frequency climate variability is the most important for the ENSO precursor